Staying Up Like a Vampire: Psychometric Validation of the Vamping Scale, Its Links to Sleep and Mental Well-Being - Yigit, Busra; Turkdogan, Esra Nur; Ergin, Kemal Feyzi; Satici, Seydi Ahmet (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2026)
Vamping refers to the intentional delay of sleep to engage in late-night activities, often involving technology use, which may impair sleep and well-being. This study adapted the Vamping Scale into Turkish and examined its psychometric properties and relationships with sleep effort, bedtime procrastination, psychological distress, and well-being.MethodsIn Study 1, 349 Turkish-speaking adults (57% female; M = 24.05 years, range = 18-68) completed the translated Vamping Scale with related sleep and procrastination measures. CFA, item-total correlations, and IRT assessed factor structure and item properties, while reliability was evaluated with alpha, omega, and lambda 6. In Study 2, 342 adults (56% female; M = 26.65 years, range = 18-56) completed the Vamping Scale with mental health and well-being measures. Pearson correlations and SEM tested whether psychological distress mediated the relationship between vamping and well-being.ResultsA revised 10-item, two-factor model showed acceptable fit (CFI = .901; SRMR = .0562) and high internal consistency (alpha = .890). Vamping was positively related to bedtime procrastination, sleep effort, and psychological distress, and negatively to life satisfaction and well-being. SEM confirmed psychological distress mediated the link between vamping and well-being.ConclusionThe Turkish Vamping Scale is a psychometrically sound instrument for assessing late-night technology use behaviors in adult populations. The findings underscore the detrimental associations between vamping, sleep-related difficulties, and psychological distress, supporting the need for targeted interventions. Future research should incorporate longitudinal designs and objective sleep measures to clarify causal pathways.
Keywords: MOBILE PHONES; MEDIA USE; ADOLESCENTS; PROCRASTINATION; PERSONALITY; QUALITY; LIFE; SATISFACTION; DEPRESSION; DURATION; Neurosciences & Neurology; Psychiatry